Diet quality and its relationship with central obesity among Mexican Americans: findings from National Health and Nutrition Examination Survey (NHANES) 1999–2012. Issue 7 (15th December 2016) - Yoshida, Yilin; Scribner, Richard; Chen, Liwei; Broyles, Stephanie; Phillippi, Stephen; Tseng, Tung-Sung
Abstract: Objective: Using the Healthy Eating Index-2010 (HEI-2010), the present study aimed to examine diet quality and the impact of overall diet quality and its components on central obesity among Mexican-American men and women. Design: Cross-sectional data from NHANES 1999–2012 were used. The HEI-2010 data, including twelve components for a total score of 100, were collected with a 24 h recall interview. Central obesity was defined as a waist circumference of ≥88 cm for women and ≥102 cm for men. Weighted logistic regressions were performed to assess associations between HEI-2010 scores and central obesity. Setting: National Health and Nutrition Examination Survey (NHANES) 1999–2012. Subjects: A total of 6847 Mexican Americans aged ≥20 years with reliable dietary recall status and non-pregnancy status. Results: Higher HEI-2010 total score was associated with lower odds of central obesity in Mexican-American men (OR; 95 % CI=0·98; 0·98, 1·00). Among all Mexican Americans, one-unit higher score of total fruit and sodium (i.e. lower level of intake) was associated with 4 % (0·96; 0·93, 0·99) and 2 % (0·98; 0·96, 0·99) lower odds of central obesity, respectively. However, a higher total proteins score was associated with higher odds of central obesity (1·08; 1·00, 1·16). In gender-specific analyses, a higher whole fruit or sodium score was inversely associated with central obesity in men but not in women. Conclusions: HEI-2010 scores of total fruit and sodium were inversely associated with central obesity among all Mexican Americans. However, total proteins score and central obesity was positively associated. In Mexican-American men, HEI-2010 total and whole fruit scores were inversely associated with central obesity.